Transition towards socially sustainable behavior? An analysis of the garment sector - Miriam Bodenheimer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
In the following case study, we will examine whether and to what degree a behavioral transition towards greater social sustainability is taking place in the garment sector. We define behavioral transitions as normatively driven changes in a conglomerate of structures, culture, norms and practices that are a key element of long-term transitions towards greater sustainability.
urn:nbn:de:0011-n-4943482
Keywords: 330